Ազգային տարազը՝ մշակութային ժառանգության կարևոր բաղկացուցիչ - Դ. Լ. Ղարիբյան (ՀՀ ԳԱԱ հրատ.)
Национальная традиция являет собой атрибут культуры, а костюм-это национально-культурный феномен, уникальный фактор, подтверждающий национальную самобытность. In the context of cultural studies, in art research done from the viewpoint of “systemic approach” only a fragmentary place is given to the National Costume.
Keywords: Geography; Anthropology; Recreation; Costume, Jewelry